Impact of Training Volunteers for Creating Awareness on Organ Donation. (July 2018) - Kumar, Pallavi; Kanvinde, Hemal; Thomas, Mareena
Abstract : Background: Public awareness is the key to improving organ donation rates in our country. Given the vast population of our country MOHAN Foundation decided to create 'foot soldiers' to work with the organization to tackle this challenging area of work. The idea of 'Angels of Change' was thus born, a unique program where volunteers are taken through a customized training module to enable them to undertake awareness initiatives on organ donation amongst various audiences. All volunteers are expected to conduct public awareness sessions thereafter. Objective: To assess the initial impact of Angels of Change volunteer training program Methods: Depending on the audience and the nature of time they are willing to commit the training is conducted as a one or two-day workshop or as weekly sessions. A comprehensive kit (standard presentation, FAQs, movie on brain death and other awareness videos) is handed over to each trained volunteer as resource available to them. The number and type of public awareness sessions conducted by the volunteers were analyzed. Special cases are highlighted. Results: Since its initiation in December 2016 till November 2017, 20 training programs have been conducted training 515 volunteers across schools, colleges and also corporate offices. The volunteers used various techniques in the 43 programs they have done: Power Point Presentation Posters Public Awareness Survey Street Plays/ Skit Human chain in public places holding posters and banners Kiosk Games Conclusion: The study focuses on the impact of training in equipping the volunteers to conduct public awareness programs. Interactions with donor families or recipients and counselors leave a lasting impact on the volunteers. Mock presentations and feedback helped volunteers to work on the content, accuracy of the information and the delivery. Highly motivated volunteers and active engagement by MOHAN Foundation staff lead to follow up awareness activities.More importantly motivated their family members to participate in the campaigns. State Bank of India Foundation. Figure. No caption available. Figure. No caption available. Figure. No caption available. Figure. No caption available.